Caracterização fenotípica de um menino com duplicação 4q associada à anomalia anorretal: relato de caso - Vitor Lucas Lopes Braga; Victoria Feitosa Muniz; Diego Silva Lima; Rosicler Pereira de Gois; Erlane Marques Ribeiro (Sociedade Brasileira de Pediatria, 2024)
Duplications of 4q represent rare chromosomal abnormalities of variable clinical features, these being directly related to the size of the duplicated segment, and whether the change was isolated or with translocation of another chromosome. Anorectal anomalies are present in a wide spectrum of birth defects, and can be isolated or syndromic, with about 60% of affected patients also having other anomalies. We present in this report a case of anorectal anomaly diagnosed at birth associated with microcephaly, facial dysmorphisms and neuropsycho-motor developmental delay. It has a normal karyotype and with the aid of the CGH-array technique it was possi-ble to diagnose this case and expand the clinical phenotype of dup4q to include the association with anorectal anomaly.